EVALUASI PENGENDALIAN INTERNAL TERHADAP KREDIT DIRAGUKAN PADA PT. BANK SULUTGO DI MINAHASA INDUK - Rotti, Marvini Rini; Manossoh, Hendrik; Kalalo, Meily Y. B. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
Credit is the most important operational activity in bank operations, where credit has the greatest asset value. Despite the risk of losses generated market business so it takes internal control to maintain corporate property and with bad loans. Good handling of credit through the company’s internal control allows for doubtful loan to smooth again. The purpose of this research is to evaluation the internal control of doubtful loan on PT. Bank SulutGo in Minahasa and whether matching with the principles of COSO. This research method is qualitative method. The technique of data collection are interview and documentation. The processing and analysis of data are done by using qualitative data and descriptive analysis. Based result the company’s management has applied the basic concept and the principle of internal control based of COSO (Committee of Sponsoring Organizations). Keywords: Internal control, doubtfull loan.